2011
DOI: 10.1099/jmm.0.027847-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing and characterization of macrolide, lincosamide and streptogramin resistance in Staphylococcus epidermidis strains isolated in a Mexican hospital

Abstract: Staphylococcus epidermidis is a normal commensal of skin that has become a serious clinical problem because of the combination of increased use of intravascular devices and an increasing number of hospitalized immunocompromised patients. In addition, there is a lack of information pertaining to resistance to macrolide, lincosamide and streptogramin type B (MLS B ) in developing countries, including Mexico. The aim of this study was to investigate the incidence of resistance to MLS B antibiotics in isolates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…The most frequent phenotypically detected mechanism of resistance to macrolide antibiotics, lincosamides and streptogramins B was the constitutive MLSB mechanism (35.8%), which agrees with the study by Lina [ 31 ] (here, it was 36.6%) and is a little less than Castro-Alarcon’s results [ 32 ] (47%) but different from Lenart-Boroń’s findings (where it was present only in 4% of the strains and where the inducible mechanism was predominant) [ 25 ]. The phenotype of resistance to erythromycin and retained sensitivity to clindamycin (MSB) was confirmed in 17 isolates (17.9%), and for Lenart-Boroń, it was 28% [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The most frequent phenotypically detected mechanism of resistance to macrolide antibiotics, lincosamides and streptogramins B was the constitutive MLSB mechanism (35.8%), which agrees with the study by Lina [ 31 ] (here, it was 36.6%) and is a little less than Castro-Alarcon’s results [ 32 ] (47%) but different from Lenart-Boroń’s findings (where it was present only in 4% of the strains and where the inducible mechanism was predominant) [ 25 ]. The phenotype of resistance to erythromycin and retained sensitivity to clindamycin (MSB) was confirmed in 17 isolates (17.9%), and for Lenart-Boroń, it was 28% [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…The gene associated with resistance to macrolides that was most often detected in our study was the msr A gene encoding a pump responsible for active efflux of the antibiotic from the cell (29.5% of the strains); the erm B gene, one of the genes encoding a methylase, was present in only 1 strain. Castro-Alarcon had contrasting results in which 32% of strains had the erm A gene [ 32 ]. The differences between the genes detected and the phenotypic detection of mechanisms of resistance may stem from testing only several selected genes – we did not look, e.g., at different variants of the msr gene, mph genes (encoding phosphotransferase), or the flax gene (responsible for resistance to lincosamides).…”
Section: Discussionmentioning
confidence: 99%
“…The results presented by Lina et al (17) show that among coagulase-negative staphylococci the inducible mechanism was detected in 28.7% of strains, while constitutive one—in 36.6%. On the other hand, Castro-Alarcon et al ( 2011 ) reported that 47% of S. epidermidis strains tested in their study showed constitutive mechanism while inducible one was detected in 8% of strains. They also determined that 16% of strains were characterized by the MS B type of resistance, while 11% showed the resistance to lincosamides.…”
Section: Discussionmentioning
confidence: 73%
“…Lenart-Boroń et al ( 2016 ) detected erm(B1) (55% of isolates) and mph(A) (9% of isolates) genes, whereas they were not observed in our study. These differences could result from different origin of the analyzed strains, since hospital isolates can acquire various genes conferring antimicrobial resistance much more frequently (Murray 2007 ; Castro-Alarcon et al 2011 ). The isolates analyzed in this study had a maximum of 7 resistance-determining genes at the same time, and some of them did not have any of the searched genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, they can be responsible for several serious infections in immunocompromised patients, particularly those associated with biomaterials (e.g., catheters, prosthetics etc. ), leading to bacteraemia and sepsis ( Ziebuhr et al 2006 , Caesy et al 2007 , Schoenfelder et al 2010 , Castro-Alarcón et al 2011 ). On the other hand, as a natural part of the microflora, drug resistant strains may be selected during antibiotic therapy, which is a potential source of the resistance genes for pathogenic strains, e.g., Staphylococcus aureus ( Reyes et al 2007 , Otto 2013 , Vitali et al 2014 ).…”
mentioning
confidence: 99%